Membongkar Egosentrisme, Eksklusivisme dan Fiksasi Agama dalam Ruang Publik - Martinus Maria Join; Irenius D. Bernad; Adrianus Naja (Parahyangan Catholic University, 2021)
The problem that has yet to find a boundary for resolution in Indonesia is how to reconcile religious pluralism. This paper focuses on the problems of religion which are often destructive, reductive and asymmetrical. Religious hegemony that dominates the public sphere is more aggressive, confrontational and egocentric than altruistic and cooperative. The tendency of religious actors to affirm their own religion better than others has triggered the emergence of various kinds of conflict. The face of religion seems to undermine Pancasila as the spirit and breath of the Indonesian people. Start- ing from this problem, the method used in this paper is the literature method. With this method the author grapples with a wealth of knowledge to restore religious life. So, as the findings of this paper, the writer presents a new paradigm that the Indonesian nation needs to be purified and restored. The Indonesian nation must receive the sacrament of reconciliation and this must become a collective consciousness of the Indonesian people. Reconciliation means being able to open oneself to forgive others and create conducive and harmonious spaces for togetherness.